Micromorphology of pejibaye leaflets Bactris gasipaes (Arecaceae) var. diamonds-10 - Sánchez-Chacón, Ethel (2016)
Bactris gasipaes is widely cultivated for the consumption of palm hearts and fruits. The present work describes the micro morphological characteristics of leaflets from adult plants of B. gasipaes, thornless variety Diamantes-10, collected in the Diamantes Experimental Station in Guápiles, Costa Rica. We collected 25 leaflets and analyses were performed with a combination of microscopy techniques: light microscopy, scanning electron microscopy and transmission electron microscopy to study their structure. Our results showed that leaflets have abundant epicuticular wax on adaxial and abaxial surfaces. Analyses from the epidermis indicated that it is composed of isodiametric cells, and it is also evident that hypodermis cells have rectangular shape and are larger than the other epidermal cells. We observed stomata on both surfaces, but they were more abundant in the abaxial surface. On the other hand, the epidermis showed the presence of trichomes with three different morphologies. In the parenchyma, cells are large and not well defined, and we observed the presence of astroesclereids, and compact groups of fiber bundles between parenchyma cells. The central vein has several vascular bundles, arranged in a continuous manner, and they are surrounded by sclerotic tissue; some of these fibers presented live protoplasts. All minor veins showed the same anatomy as the central vein. In these veins, the vessel elements of protoxylem and metaxylem showed scalariform ornaments on their walls. Phloem is located towards the adaxial surface of the vein and we observed sieve and companion cells surrounded by fibers and parenchyma cells. The companion cells presented branched plasmodesmata attached to a sieve element, and in these elements we found protein bodies called P-protein. The main anatomical difference in the leaflets of the var. Diamantes-10, compared to the other varieties of B. gasipaes K, is the lack of thorns; the other morphological features seem to be conserved.